الشيخ عبد الله بن فودي ومنهجه في التعامل مع الأحاديث النبوية في تفسيره "ضياء التأويل في معاني التنزيل" سورة البقرة نموذجاً - ماداكي، زبير أبو بكر (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The research intends to narrate the biography of one of Nigeria's famous black interpreters of the Holy Qur'an, that is Sheikh Abdullahi bin Muhammad Fodio (1232AH/1817AD), who was the first to write the Qur'anic Exegesis. Additionally, he wrote many other books close to 170 in number so the research discusses his contributions, by sword or pen, in spreading Allah's words in Nigeria. The research also examines his famous exegesis “Dhiya'u at-Ta'awil fi Ma'ani at-Tanzil” and concentrates on how the author approaches the Prophetic traditions in his Tafsir. The Tafsir is spread among Nigerians and its neighbouring countries but there is no single research on this topic. For this purpose, the research explains his approach and analyzes how he narrates or deals with Ahadith; the authentic as well as the weak ones, the reasons for revelation, the importance of some verses, etc. In addition, the Hadith which exempts, abides or elaborates on the verses from the Holy Qur'an are also discussed with some examples taken from the Surah Al-Baqarah as the model with their authentication. This work will benefit students as a contemporary Islamic view.